Composite Materials Processing, Applications, Characterizations - Kar, Kamal K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
Composite materials are used as substitutions of metals/traditional materials in aerospace, automotive, civil, mechanical and other industries. The present book collects the current knowledge and recent developments in the characterization and application of composite materials. To this purpose the volume describes the outstanding properties of this class of advanced material which recommend it for various industrial applications.
Selected Topics on Composite Materials: Recent Developments -- Polymer Based Composite Structures: Processing and Applications -- Polymer Based Composite Materials: Characterizations -- Newly Developed Rubber Pressure Molding Technique for Fabrication of Composites -- Functionally Graded Composites: Processing and Applications -- Nano Micro Composites by Electrodeposition -- Short Carbon Fiber Reinforced Polycarbonate Composites -- Ionic Polymer Metal Composites -- Nanocomposites Based on Carbon Nanomaterials and Electronically Nonconducting Polymers -- Syntactic Foams For Multifunctional Applications -- Advanced Carbon-Carbon Composites: Processing Properties and Applications -- Metal Matrix Composites: Theory, Techniques and Applications -- Functionally Graded Styrene Butadiene Rubber Composites with Gradation of Magnetic Properties -- Mechanical, Electrical and Tribological Properties of Copper-Graphite Composites -- Current Advancements in Ceramic Matrix Composites -- Advanced ZrO2-based Ceramic Nanocomposites for Optical and other Engineering Applications -- xAgI-(1-x)MPO3 [M=Ag, Li) Superionic Composite Glasses and Their Current Issues -- Carbon Nanotube/Graphene Reinforced Ceramic Composites -- Bamboo Fiber Based Polymer Composites -- Superhydrophobic and Superoleophobic Surfaces.
Keywords: Materials science; Materials; Materials Science; Materials Engineering